The Family Alliance Model: A Way to Study and Characterize Early Family Interactions - Favez, Nicolas; Frascarolo, France; Tissot, Hervé (Frontiers in Psychology, 2017)
The aim of this paper is to present the family alliance (FA) model, which is designed to conceptualize the relational dynamics in the early family. FA is defined as the coordination a family can reach when fulfilling a task, such as playing a game or having a meal. According to the model, being coordinated as a family depends on four interactive functions: participation (all members are included), organization (members assume differentiated roles), focalization (family shares a common theme of activity), affect sharing (there is empathy between members). The functions are operationalized through the spatiotemporal characteristics of nonverbal interactions: for example, distance between the partners, orientation of their bodies, congruence within body segments, signals of readiness to interact, joint attention, facial expressions. Several standardized observational situations have been designed to assess FA: The Lausanne Trilogue Play (with its different versions), in which mother, father, and baby interact in all possible configurations of a triad, and the PicNic Game for families with several children. Studies in samples of nonreferred and referred families (for infant or parental psychopathology) have highlighted different types of FA: disorganized, conflicted, and cooperative. The type of FA in a given family is stable through the first years and is predictive of developmental outcomes in children, such as psychofunctional symptoms, understanding of complex emotions, and Theory of Mind development.